2020
DOI: 10.20944/preprints202010.0482.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional Regulation of Inflammasomes

Abstract: Inflammasomes are multimolecular complexes with potent inflammatory activity. As such, their activity is tightly regulated at the transcriptional and post-transcriptional levels. In this review, we present the transcriptional regulation of inflammasome genes from sensors (e.g NLRP3) to substrates (e.g. IL-1β). Lineage-determining transcription factors shape inflammasome responses in different cell types with profound consequences on the responsiveness to inflammasome-activating stimuli. Pro-inflammato… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 105 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…Inflammasomes are multiprotein complexes that promote the availability of pro-inflammatory cytokines, such as interleukin-1β and interleukin-18. 49,50 Among various inflammasome complexes, the NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome can contribute to secondary brain damage 51 and is activated in rodent models of epilepsy, [52][53][54][55][56][57] and in humans with a seizure disorder. 36,[57][58][59][60][61] A recently-published review provides additional details, 62 and another suggests inflammasomes might be good targets for therapeutic intervention.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
See 2 more Smart Citations
“…Inflammasomes are multiprotein complexes that promote the availability of pro-inflammatory cytokines, such as interleukin-1β and interleukin-18. 49,50 Among various inflammasome complexes, the NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome can contribute to secondary brain damage 51 and is activated in rodent models of epilepsy, [52][53][54][55][56][57] and in humans with a seizure disorder. 36,[57][58][59][60][61] A recently-published review provides additional details, 62 and another suggests inflammasomes might be good targets for therapeutic intervention.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…However, inflammatory cascades are complex incorporating interconnected sets of networks. 50,198 Consequently, interfering in the function of just one component can sometimes appreciably reduce the extent and severity of inflammation. 199 More than a decade ago, antibodies that neutralize a single cytokine were known to have broad anti-inflammatory effects.…”
Section: Specific Anti-inflammatory Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Recognition of microbial ligands by Toll-like receptors (TLRs) and the stimulation of cytokines such as TNFα trigger nuclear factor kappa (NF-κB) to upregulate NLRP3, pro-caspase-1, and pro-IL-1 transcription ( Figure 1C ). 21 , 22 A study by Toldo et al found that the priming stage is required for NLRP3 inflammasome activation and that even overexpression of NLRP3 (constitutively active) cannot activate caspase-1 when pro-caspase-1 is insufficient. 23 The second step is the activation of the inflammasome complex by the oligomerization of NLRP3 and the recruitment of ASC and pro-caspase-1.…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%
“…We revealed significant expression changes in ivLIMs at day 3 PI compared to non-infected controls in 88 transcripts for TFs or TF components, most of which were reduced in abundance following infection (Figure 6), including members of the AP1 complex and the NF-kB family previously linked to cell death gene expression (Ameyar et al;Barkett and Gilmore, 1999). A direct link between the reduced TF abundance and the dichotomic expression changes in LIMs could be established for (i) stat1 and trp53 regulating caspase gene expression (Chin et al, 1997;Gupta et al, 2001;Xu et al, 2014), (ii) trp53 controlling expression of fas, bbc3, ppmaip1, bcl2l11 and bax ( (Aubrey et al, 2018), (iii) ppar γ, which is increased during infection and inhibits the expression of proapoptotic bax (Arnett et al, 2018), and iv) NF-κB transcription factor family that regulates birc2, nlrp3, pycard and il1β and is itself inhibited at various levels during Leishmania infection (Cornut et al, 2020;Lecoeur et al, 2021;Lecoeur et al, 2020a). Reduced expression of NF-κB family members is likely regulated at epigenetic levels as we have previously shown for L.am-infected BALB/c macrophages (Lecoeur et al, 2020a).…”
Section: Pan-rcd Inhibition In Ivlims Correlates With Important Chang...mentioning
confidence: 99%